2012
DOI: 10.1136/sextrans-2012-050610
|View full text |Cite
|
Sign up to set email alerts
|

Cervical human papillomavirus detection is not affected by menstrual phase

Abstract: Objectives In many settings, human papillomavirus (HPV) DNA testing already plays an important role in cervical cancer screening. It is unclear whether hormonal fluctuations associated with menstrual phase or oral contraceptive (OC) use have any effect on HPV detection. We evaluated the effects of OC use and timing of cervical sampling in relation to women’s last menstrual period (LMP) on HPV detection, and viral load in the Brazilian Ludwig-McGill cohort study. Methods Women in the cohort were followed ever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…Another study found all HPV DNA likely peaks at the periovulatory phase (Liu et al, 2013). However, no correlation was found in Tota's study (Tota et al, 2013). In our current study, even with a small number of animals, we found that animals at the oestrous stage, the only stage at which the animals mate, had the highest viral DNA load in the vaginal lavage samples.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…Another study found all HPV DNA likely peaks at the periovulatory phase (Liu et al, 2013). However, no correlation was found in Tota's study (Tota et al, 2013). In our current study, even with a small number of animals, we found that animals at the oestrous stage, the only stage at which the animals mate, had the highest viral DNA load in the vaginal lavage samples.…”
Section: Discussioncontrasting
confidence: 75%
“…HSV shedding did not vary with the menstrual cycle, but CMV shedding was significantly more frequent in the luteal phase (Mostad et al , 2000). The correlation between HPV detection and menstrual cycle has been inconsistent in the literature (Liu et al , 2013; Schmeink et al , 2010; Tota et al , 2013). In one study, HR HPV detection was significantly influenced by sample timing in the menstrual cycle (Schmeink et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings agreed with reports in the literature that progesterone hormones increase viral mRNA and significantly stimulate viral replication [ 39 , 64 , 65 ]. Studies on the relationship between contraceptive use and HPV infections have produced discordant findings in humans [ 27 , 55 , 66 , 67 ]. A recent study showed that contraceptives did not increase the risk of acquiring new HPV infections [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that contraceptives did not increase the risk of acquiring new HPV infections [ 27 , 28 ]. Some published studies postulate that sex hormone use could have a protective effect, depending on age: frequent acquisition of infections by different papillomavirus types may stimulate immunologic control in a young age group [ 67 ]. However, the continuous stimulatory effect of the hormones on expression of the papillomavirus genes could also lead to an increase in expression of the viral oncogenes, i.e., E6 and E7, thereby enhancing their transforming potential.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, the relationship between viral shedding and infectivity remains murky. A related issue is explored by Franco et al 11 in a study which explores HPV shedding through the menstrual cycle. Like gonorrhoea, the biology and epidemiology of HPV will continue to evolve.…”
mentioning
confidence: 99%